Trapping and the Detection, Control, and Regulation of Tephritid Fruit Flies 2014
DOI: 10.1007/978-94-017-9193-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Plant Odors as Fruit Fly Attractants

Abstract: Plant odors consist of a mixture of volatile compounds that are conveyed by diffusion through air and may disperse over a long distance. They play a major role in mediating insect-plant relationships, particularly food location and selection of suitable sites for mating or oviposition. This chapter presents state-of-the-art research on the response of fruit flies (Diptera, Tephritidae) to plant odors and their potential for the development of trapping systems. Main research results from Tephritids of economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 146 publications
0
21
0
Order By: Relevance
“…B. carambolae represented 24.9 and 21.3% of all fruit flies reared from fruit collected in Calçoene and Oiapoque, respectively, with a higher abundance in coinfested fruit ( Table 2 ). Several studies have demonstrated that species within the dorsalis complex have a marked preference for ripe fruit (cf Alyokhin et al 2000 , Cornelius et al 2000 , Rattanapun et al 2009 , Quilici et al 2014 ). Even though B. carambolae belongs to the dorsalis complex, there are no studies on the influence of the degree of fruit ripeness on female oviposition decision in this species.…”
Section: Discussionmentioning
confidence: 99%
“…B. carambolae represented 24.9 and 21.3% of all fruit flies reared from fruit collected in Calçoene and Oiapoque, respectively, with a higher abundance in coinfested fruit ( Table 2 ). Several studies have demonstrated that species within the dorsalis complex have a marked preference for ripe fruit (cf Alyokhin et al 2000 , Cornelius et al 2000 , Rattanapun et al 2009 , Quilici et al 2014 ). Even though B. carambolae belongs to the dorsalis complex, there are no studies on the influence of the degree of fruit ripeness on female oviposition decision in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Such ecological factors were suggested to form a composite predation and hot spot effect, modulated by microclimate preferences in habitat selection, such as trees with denser canopies that provide better shade and shelter (Field, Kaspi, & Yuval, ). Medfly male spatial distribution might often be affected also by plant volatiles, especially the male attractant terpene α‐copaene (Juan‐Blasco et al., ; Quilici, Atiama‐Nurbel, & Brévault, ; Shelly, ), which can demonstrate high variability both between individual trees and even within trunk and branches of specific trees (Shelly & Villalobos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Current management strategies for medfly include the use of trimedlure-baited traps for pest detection and monitoring and the release of sterile male flies for population suppression [2,3,4,10,11,12]. Trimedlure, tert-butyl 4(and 5)-chloro-2-methylcyclohexane- l-carboxylate (C 12 H 21 ClO 2 ), is a synthetic attractant with a mixture of different diastereomers.…”
Section: Introductionmentioning
confidence: 99%
“…Trimedlure, tert-butyl 4(and 5)-chloro-2-methylcyclohexane- l-carboxylate (C 12 H 21 ClO 2 ), is a synthetic attractant with a mixture of different diastereomers. Of these isomers, (+)-trimedlure-C was found to be the most attractive [12]. The development of male lures for C. capitata has a long history of success.…”
Section: Introductionmentioning
confidence: 99%